HUBUNGAN TINGKAT STRES DENGAN DERAJAT NYERI DISMENORE PRIMER PADA REMAJA PUTRI KELAS 10 SMAN 1 BANJARAN KABUPATEN BANDUNG - sri ayu lestari, Ade Irma; Meliyanti, Mira (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
Stress is the body's response to situations of pressure, threat, or change that come from within or outside. Stress is one of the factors that can cause dysmenorrhea. Dysmenorrhea is pain felt in the lower abdomen or cramps before menstruation that lasts 2-3 days, starting the day before menstruation begins. Stress can cause blood flow to be disrupted so that there is oxygen deficiency in the uterus (ischemia) and increase production and stimulate prostaglandins in the uterus, causing dysmenorrhea. This study aims to determine the relationship between Stress Levels and the Degree of Primary Dysmenorrhea Pain in Adolescents Girl of Class X SMAN 1 Banjaran. The type of correlation research, the population of this study was Adolescent Girls of Class X SMAN 1 Banjaran with a sample of 55 respondents and the sampling technique used a simple random sampling approach. The research instrument for stress levels used DASS (Depression Anxiety Stress Scale) and for Dysmenorrhea used the Numeric Rating Scale (NRS) Questionnaire. Bivariate analysis used Spearman rank. The results of the study showed that there was a moderate stress level category of 29 respondents (52.7%), a moderate dysmenorrhea pain level category of 25 respondents (45.5%) out of a total of 55 respondents and there was a relationship between stress levels and the degree of dysmenorrhea pain in female adolescents in grade X of SMAN 1 Banjaran (p = 0.000 and a correlation coefficient of 0.504) so there was a fairly strong/moderate relationship. Suggestions for schools should provide a counseling place for adolescents who experience complaints related to adolescent reproduction because many adolescents are still embarrassed to consult directly with health services.